Pembelajaran â€œProjek IPASâ€ Berbasis STEAM sebagai Kajian Implementasi Kurikulum Merdeka di SMK - Muhammad Syaipul Hayat; Sumarno Sumarno; Mahmud Yunus; Noora Qotrun Nada (Postgraduate, University of Mataram, 2023)
The implementation of the Independent Curriculum in SMK requires science learning to be carried out across disciplines through projects. This study aims to examine the potential and implementation of learning